Perception of Men Who Have Sex with Men about the Test and Treat Strategy of Human Immunodeficiency Virus in Bandung City - Ayesha Nadiatama Saifuddin; Nita Arisanti; Bony Wiem Lestari (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Human immunodeficiency virus (HIV) infection in Indonesia has shifted from injecting drug use to sexual transmission. One of the ways to prevent HIV transmission is by using early antiretroviral therapy (ART) or known as Test and Treat. Test and Treat is recommended by the World Health Organization (WHO) in 2013. This study aimed to explore the perception of men who have sex with men (MSM) about HIV Test and Treat Strategy. Methods: This quantitative observational study used a cross-sectional design. Primary data were collected from questionnaires filled in by 58 MSM diagnosed as HIV positive at Mawar Clinic, Pasundan and Ibrahim Adjie public health centers in September–December 2016. Sampling was performed using total sampling method which was bounded by time period. The questionnaire contained data of respondents’ characteristics and perceptions of HIV Test and Treat Strategy. Data analysis was presented in tables. Result: Respondents were mostly 20–24 years old (48%), 55% were Senior High School graduates, 98% were unmarried, 58% worked as employees, and 21% earned 2–2.5 million rupiahs per month. Forty eight percent of the respondents had negative perception of the test and treat strategy, and 52% of the respondents had positive perception of the strategy.Conclusions: Most of the MSM population have a negative perception of HIV test and treat strategy. It is important for the key populations especially the MSM to obtain education related to HIV treatments and strategy.